SISTEM INFORMASI GEOGRAFIS BERBASIS WEB LAYANAN BANTUAN LANGSUNG TUNAI DESA AIR TENANG, KECAMATAN AIR HANGAT, KABUPATEN KERINCI - Anggun Myanti Fitri; Arie Yulfa (JURNAL BUANA, 2026)
This study aims to identify the functions needed to create a WebGIS system for Air Tenang village cash transfer assistance which is then implemented in the WebGIS design for Air Tenang village cash transfer assistance. This research is a development research known as Research & Development (R & D) using the waterfall model with stages, i.e systems engineering, system analysis, system design, implementation, system evaluation, operation and maintenance. The results of the study show that the functions needed in making WebGIS services for Air Tenang village cash transfer service include displaying information, managing data (input, editing and deleting) and requesting assistance services. Development of a WebGIS for village cash transfer services resulted in a WebGIS system with the domain address http://2022-webgispenerimabltdesa.000webhostapp.com/ . This WebGIS system has been tested on village communities, the result shows that the majority of respondents consider that the work of the system is satisfactory and can be applied by village side as an alternative in village cash transfer program.